A global systematic review on orchid data in Protected Areas - Khapugin, Anatoliy A. (Nature Conservation Research: Заповедная наука, 2020)
A systematic global literature review of studies devoted to Orchidaceae taxa in Protected Areas is presented here. It is aimed to understand research topics of studies on orchids in Protected Areas around the world. Used is the methodology well established in biological and medical science with a focus on two international databases (Scopus, Web of Science Core Collection) and one national (Russian Science Citation Index). Examined are the data on each paper's Protected Area location, habitat studied, topic discussed, and IUCN status of each Protected Area. It is hypothesised that orchids are predominantly investigated in Protected Areas, and therefore, the published results of studies on orchids are properly indexed by databases globally. The question is whether the most threatened plants, orchids, would be investigated in more detail and intensity in areas legally protected by authorities (nature reserves, national parks, natural monuments, wildlife sanctuaries, etc.), and whether the databases Scopus, Web of Science Core Collection, Russian Science Citation Index cover appropriately the majority of papers on orchids in Protected Areas on a global scale. There were found 331 publications on orchids in Protected Areas, including 72 from RSCI, 96 from Scopus, 163 from Web of Science Core Collection. A high percentage of the studies were conducted in the tropics, while vast temperate and subtropical regions (Northern Eurasia, Central and Western Asia, Northern and Central parts of North America, non-tropical Africa, and most parts of Australia) were poorly represented. Most studies were conducted in forests (in descending order of abundance – tropical, temperate, boreal), and were focused predominantly on the diversity and distribution of orchids in Protected Areas, followed by issues of taxonomy, structure and population dynamics, conservation threats of Orchidaceae, and orchid-consort interactions (insects-pollinators, trees-phorophytes, symbiotic fungi). It is concluded that the use of only the databases Scopus, Web of Science Core Collection and Russian Science Citation Index does not provide a sufficient amount of data to generalise comprehensive data about studies of orchids in Protected Areas at a global scale. In future systematic reviews of other, in non-English-language, international and national databases should be carried out.